Assessing the effectiveness of academic development programmes: A statistical analysis of graduation rates across three programmes - Smith, Leonard C; Case, Jennifer M; van Walbeek, Corne (South African Journal of Higher Education, 2016)
This study uses statistical analysis to estimate the impact of the first-year academic development (AD) courses offered by the University of Cape Town’s three largest AD programmes, in the faculties of Commerce, Engineering and Science, on the graduation performance of AD students relative to that of mainstream students. The study furthers research in the area on three counts. Firstly, it considers three diverse AD programmes. Secondly, the data for five cohorts (1999‒2003) is pooled, and multivariate analysis (MVA) is used to identify the key determinants of academic performance for AD and mainstream students. Finally, a more comprehensive specification is estimated than in previous studies. We find that AD programmes, as they were constituted during the period under investigation, did not meet the objective of improving the graduation rate achieved by AD students relative to their peers on the mainstream. We suggest two possible courses of action in the light of our findings: (1) Universities could extend AD courses into the second and third years, or (2) tertiary institutions could modify their mainstream programmes such that they are better able to meet the epistemological, educational and psychological needs of their students.